Association Study between Functional Polymorphisms of MMP9 Gene Promoter and Multiple Sclerosis Susceptibility in an Iranian Population - Sima SABBAGH; Zakiye NADEALI; Leila DEHGHANI; Vahid SHAYGANNEJAD; Majid REZVANI; Masih SABOORI; Hamid GANJI; Soheil TAHANI; Farzaneh DEHGHANI; Saman HOSSEINZADEH; Elnaz MARZBANI; Peiman SHAFIEI (Tehran University of Medical Sciences, 2019)
Background: Matrix metalloproteinase-9 (MMP-9) polymorphisms, C−1562 T and -90 (CA) n repeats, which influence transcriptional activity of this gene, are proposed to play a role in MS susceptibility and its development. In the present study, the possible association of MMP-9 polymorphisms in Iranian MS patients is studied. Methods: Association of MMP-9 mentioned gene polymorphisms with MS susceptibility was evaluated in unrelated Iranian subjects referred to Al-Zahra Hospital, Isfahan, Iran during 2014 to 2017.  Results: -1562 T allele of MMP-9 was associated with increased MS risk. However, we found no overall significant effect of −90 (CA)n repeat on MS susceptibility. Conclusion: For as much as MMP-9 molecule is a potential target for MS therapy, to determine whether any of MMP-9 polymorphisms influence MS susceptibility in Iranian MS patients or not, concerning the significant influence of T allele on MS susceptibility and the non-significant association regarding CA repeats, further research is needed before proposing any definite conclusion.